2019
DOI: 10.5812/jkums.85256
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antioxidant and Antimicrobial Properties of the Essential Oil of Hyssopus officinalis L

Abstract: Background:Medicinal plants and their extracts are extensively used in nutrition, medicine and food industry. These plants are considered the most important natural antimicrobial antioxidants since they provide rich sources of phenolic compounds, and if resuscitated, they prevent the oxidation process. Objectives: The present study was conducted to investigate the antimicrobial and antioxidant properties of Hyssopus officinalis essential oil as a chemical preservative. Methods: The Hyssopus officinalis plant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Since the Plants with high potential from secondary metabolites and compounds such as phenolic compounds, flavonoids, alkaloids [3][4][5] , may be able to help and improve the recovery of patients, therefore in this study we reviewed the properties of 12 herbal extracts or infusions among 50 plant species which could have improved recovery quality in COVID-19 affected patients. The method of plant selection was based on past studies, active ingredients and therapeutical properties on viruses [6][7][8][9][10][11][12] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the Plants with high potential from secondary metabolites and compounds such as phenolic compounds, flavonoids, alkaloids [3][4][5] , may be able to help and improve the recovery of patients, therefore in this study we reviewed the properties of 12 herbal extracts or infusions among 50 plant species which could have improved recovery quality in COVID-19 affected patients. The method of plant selection was based on past studies, active ingredients and therapeutical properties on viruses [6][7][8][9][10][11][12] .…”
Section: Methodsmentioning
confidence: 99%
“…One-third of the HCP used a single source of information. HCP agreed on the importance of an e-learning app and their expectations regarding its content and utility of this were classified as follows, on a 10 point scale: obtaining an answer quickly while facing poisoning cases (8), finding the information required as fast as possible (8), recognizing the common syndromes (8), assessing the seriousness (8), knowing the routine dosage and their interpretation (7) and managing the case on their own (7). One-third of the respondents did not want to pay for a clinical toxicology app (35%) and more than one-third accepted to pay only if it includes certified training for continuing medical education (40%).…”
Section: P10-02mentioning
confidence: 99%
“…Many publications are devoted to the study of the species H. officinalis L. growing in European, Asian and African countries. The component composition and quantitative content of various constituents in essential oils may vary depending on soil, climatic and genetic factors [ 12 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]; however, the main ketones that are characteristic of this species are pinocamphone 1 and cis-pinocamphone 2 (their relative content varies ranging from 2.94 to 63.55%; these components are in dynamic equilibrium), α-pinene 3 and β-pinene 4 , sabinene 5 , myrcene 6 , phellandrene 7 , linalool 8 , myrtenol 9 , elemol 10 and germacrene-D 11 ( Figure 1 ).…”
Section: Mono- and Sesquiterpenoids Of Essential Oils From Plants Of ...mentioning
confidence: 99%
“…Essential oils, due to their broad applicability in various industries, like pharmacy or food industries, have received much attention [23,24]. Furthermore, more comprehensive studies of essential oils revealed their potential in environmental-friendly horticultural disease management as they have antiseptic, antiviral, antibacterial, and antifungal properties [25,26]. Additionally, essential oils, as secondary metabolites, exhibit high plant defence effects, are non-toxic, biodegradable, and limit pathogenic organisms [24,27].…”
Section: Introductionmentioning
confidence: 99%